Open source systems for business rules repository development - Čeponis, Lauras; Vasilecas, Olegas (Lietuvos matematikos rinkinys, 2005)
Rules repository is used to store rules and track changes of them. It is an importand part of rules management system. Currently no open source products are available. In this paper we disscuss a possibility to use open source repository system FEDORA. Architecture level insight proves that the repository system FEDORA can be used to manage descriptions of rules and relationships between them. When the information schema is adapted, general capabilities of the repository system can be used.